2022
DOI: 10.1007/s10841-022-00402-6
|View full text |Cite
|
Sign up to set email alerts
|

Scale-dependent effects of landscape context on urban bee diversity

Abstract: As urbanization continues throughout much of the world, there is great interest in better understanding the value of urban and residential environments to pollinators. We explored how landscape context affects the abundance and diversity of bees on 50 residential properties in northern Georgia, USA, primarily in and around Athens, GA. Over 2 years of pan trap sampling we collected 4938 bees representing 111 species, from 28 genera in five families, constituting 20% of the species reported for the state. Develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…In some cases, opposite conclusions can be reached about the relationship between forest cover and pollinator diversity depending on the scale investigated. In the southeastern USA, for example, Janvier et al (2022) found urban bee diversity to be negatively related to the amount of forest within the surrounding 250 m but positively related to forest cover at 2 km. Similarly, in Brazil, Montagnana et al (2021) reported a positive effect of forest cover on bee diversity at large scales (5 km) but found landscape heterogeneity to be more important at the local scale (1 km).…”
Section: Local Effects Of Forest Cover Are Scale Taxon and Context De...mentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, opposite conclusions can be reached about the relationship between forest cover and pollinator diversity depending on the scale investigated. In the southeastern USA, for example, Janvier et al (2022) found urban bee diversity to be negatively related to the amount of forest within the surrounding 250 m but positively related to forest cover at 2 km. Similarly, in Brazil, Montagnana et al (2021) reported a positive effect of forest cover on bee diversity at large scales (5 km) but found landscape heterogeneity to be more important at the local scale (1 km).…”
Section: Local Effects Of Forest Cover Are Scale Taxon and Context De...mentioning
confidence: 99%
“…In the southeastern USA, for example, Janvier et al . (2022) found urban bee diversity to be negatively related to the amount of forest within the surrounding 250 m but positively related to forest cover at ~2 km. Similarly, in Brazil, Montagnana et al .…”
Section: Local Effects Of Forest Cover Are Scale Taxon and Context De...mentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, there is increasing interest in planting for pollinators (Braman and Griffin, 2022). A recent study (Janvier et al, 2022) reported results from pan trap sampling 50 residential sites in and around Athens, Clarke Co., GA and documented 110 species of bees occurring in these urban and peri urban habitats. Twentytwo of the bee species collected directly from flowers reported in the present study were also represented in Janvier et al, thus further demonstrating the similarity and reliability of our collection methods.…”
Section: Discussionmentioning
confidence: 99%
“…Using the gBuffer function of the 'rgeos' package (59), we calculated the proportion of forest in the landscape surrounding each site at 10 spatial scales (from 200 to 2000 m, using 200 m increments), hereafter referred to as landscape forest cover (LFC). These spatial scales are appropriate for bee community responses to multi-scale landscape factors (60) and are within accepted distances of bee dispersal and foraging (55,61). We used Pearson correlation between species richness and LFC at all scales to determine the spatial scale at which most species respond (62; Supplementary Table S5).…”
Section: Landscape Data and Spatial Scalementioning
confidence: 99%